ZFAS1: a long noncoding RNA associated with ribosomes in breast cancer cells - Hansji, Herah (Biol Direct, 2016)
BACKGROUND: Most of the eukaryotic genome is transcribed, yielding a complex network of transcripts including thousands of lncRNAs that generally lack protein coding potential. However, only a small percentage of these molecules has been functionally characterised, and discoveries of specific functions demonstrate layers of complexity. A large percentage of lncRNAs is located in the cytoplasm, associated with ribosomes but the function of the majority of these transcripts is unclear. The current study analyses putative mechanisms of action of the lncRNA species member ZFAS1 that was initially discovered by microarray analysis of murine tissues undergoing mammary gland development. As developmental genes are often deregulated in cancer, here we have studied its function in breast cancer cell lines. RESULTS: Using human breast cancer cell lines, ZFAS1 was found to be expressed in all cell lines tested, albeit at different levels of abundance. Following subcellular fractionation, human ZFAS1 was found in both nucleus and cytoplasm (as is the mouse orthologue) in an isoform-independent manner. Sucrose gradients based on velocity sedimentation were utilised to separate the different components of total cell lysate, and surprisingly ZFAS1 was primarily co-localised with light polysomes. Further investigation into ribosome association through subunit dissociation studies showed that ZFAS1 was predominantly associated with the 40S small ribosomal subunit. The expression levels of ZFAS1 and of mRNAs encoding several ribosomal proteins that have roles in ribosome assembly, production and maturation were tightly correlated. ZFAS1 knockdown significantly reduced RPS6 phosphorylation. CONCLUSION: A large number of lncRNAs associate with ribosomes but the function of the majority of these lncRNAs has not been elucidated. The association of the lncRNA ZFAS1 with a subpopulation of ribosomes and the correlation with expression of mRNAs for ribosomal proteins suggest a ribosome-interacting mechanism pertaining to their assembly or biosynthetic activity. ZFAS1 may represent a new class of lncRNAs which associates with ribosomes to regulate their function. REVIEWERS: This article was reviewed by Christine Vande Velde, Nicola Aceto and Haruhiko Siomi. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13062-016-0165-y) contains supplementary material, which is available to authorized users.